Exploring strategies for promoting engagement in EFL classes at primary schools: Insights from Vietnamese teachers - Trang Le Diem Bui; Dao Thi Thuy Nguyen; Truc Thi Thanh Ly (Studies in English Language and Education)
This study explores the strategies used by English as a foreign language (EFL) primary school teachers to promote engagement among young learners in the classroom and examines how these strategies manifest across the behavioral, emotional, cognitive, and social dimensions of learner engagement. Six EFL teachers from five primary schools in the South of Vietnam participated in this study. Data were collected through multiple qualitative methods, including classroom observations (two 35–40-minute full-length lesson videos per teacher), field notes, stimulated recall sessions, and semi-structured interviews.  Thematic analysis was conducted to identify recurring patterns in teacher practices aimed at promoting engagement. This process involved systematic coding of the data using an inductive approach. Triangulation of multiple data sources revealed a wide range of strategies employed by teachers to enhance different aspects of engagement among young EFL learners, with a predominant focus on the behavioral and emotional dimensions and comparatively less attention to cognitive and social dimensions. These results provide insights into the practices of teachers in engaging young learners in primary school classrooms and highlight the need for a balanced use of strategies across all dimensions of engagement. The findings suggest that teacher training programs should emphasize the importance of addressing all dimensions of learner engagement, encouraging a more comprehensive approach to fostering engagement in the classroom.